(untitled) (Latakia University Journal -Engineering Sciences Series, 2019)
هذا العمل يقترح طريقة بسيطة للتحكم بالمرشح الفعال من خلال استخدام المنظم التقليدي PI (Proportional Integral ) للحصول على إشارة خرج بأقل خطأ استاتيكي ممكن. إن طريقة التحكم المقترحة بتيار خرج المرشح الفعال تستخدم إشارة دخل (كإشارة مرجعية) عبارة عن إشارة في المحاور d-q من خلال تحويل إشارة التيار الفعلية المتناوبة ثلاثية الطور a, b, c وذلك لتعويض التوافقية الخامسة 5th والسابعة 7th. وبينت الدراسة بالنمذجة والتطبيق المخبري أن المرشح الفعال يعمل بفعالية ودقة جيدة لإلغاء التوافقية الخامسة والسابعة الناجمتين عن الأحمال اللاخطية. This paper proposes a simple current control for Active Filters based P+Resonant compensator used in conjunction with traditional (Proportional Integral) PI. The proposed current control system is designed to operate with a single dq reference frame, synchronous with 50 Hz supply voltage, for the compensation of 5th and 7th harmonics. Another major advantage of this strategy is the ability to eliminate the external disturbance from the 5th and 7th harmonic components caused by power supply. The principle of the proposed control method and the design procedure is here presented. Simulation and experimental results confirm the effectiveness of the suggested approach.